Ще раз про етнічний склад населення Ольвії в перших століттях н. е. - Зубар, В.М. (Археологія, 1996)
В статті розглядаються деякі питання етнічного складу населення Ольвії в перших століттях н. е., від вирішення яких буде залежати вірне розуміння цілого комплексу проблем, пов'язаних з історичним розвитком цього античного центру в зазначений період. В статье на базе имеющихся источников автор приходит к заключению, что после гетского нашествия этнический состав жителей Ольвии изменился вследствие включения в воссозданную гражданскую общину значительного количества выходцев из сильно эллинизированного этнического массива жителей нижнеднепровских городищ. В результате этого в Нижнем Побужье складывается новая этническая общность — борисфениты, что наиболее ярко проявилось в ономастике Ольвии. Сейчас достаточно уверенно можно говорить об определенной специфике этнических процессов в Ольвии на рубеже и в первых веках н. э. Естественно, более углубленное исследование затронутых в статье вопросов — дело будущего, но и на имеющемся материале, как представляется, все же можно констатировать специфические отличия этнического развития населения Нижнего Побужья от других античных центров в первые века н. э. А это в свою свидетельствует о многообразии и неповторимости этнической истории античных государств Северного Причерноморья и заставляет строго дифференцировано подходить к материалу из различных греческих городов, с учетом специфики конкретно-исторического развития каждого региона. Это в конечном итоге и позволит выявить не только общее, но и особенное в их исторических судьбах. On the basic of the sources available the author comes to the conclusion that the ethnic composition of the Olbian population changed after invasion of the Gets as a result of incorporation of the considerable number of representatives from the highly hellinized ethnic group of inhabitants of the Lower-Dnieper settlements to the reconstructed civil community. That gave rise to a new ethnical community, namely, Borisphenites, in the territory of the lower Bug reaches. It is exhibited most vividly in onomastics of Olbia. At present, we may dwell rather confidently on a definite specificity of ethnic processes in Olbia on the border and in the first centuries A. D. The problems touched in the paper wait for their more comprehensive study in the future, but it seems that even findings available permit identifying specific properties of ethnic development which differ population of the lower Bug territory from population of other antiques centers in the first centuries A. D. This fast, in its turn, proves variability and uniqueness of ethnic history of antiques states located in the Northern Black Sea coastal territory and makes it necessary to treat strictly differently the findings from various Greek towns taking into account specificity of particular historic development of each region. Finally, this will make it possible to reveal not only common properties in their historic fortunes, but distinctions as well.